2018
DOI: 10.1177/0047287518794319
|View full text |Cite
|
Sign up to set email alerts
|

Postdisaster Social Capital, Adaptive Resilience and Business Performance of Tourism Organizations in Christchurch, New Zealand

Abstract: The resilience of tourism organizations is an important issue for destinations. While studies examine the social capital of firms, researchers have yet to understand the relationship between social capital (structural, relational and cognitive) and organizational resilience as predictors of business performance. This study evaluates these relationships at the interfirm level among tourism organizations in the postdisaster context of Christchurch, New Zealand, where business performance for some tourism operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 116 publications
(264 reference statements)
3
107
0
2
Order By: Relevance
“…The vulnerability of the tourism sector justifies the growing interest in the literature on the topic of resilience (e.g., Chowdhury, Prayag, Orchiston, & Spector, 2019 ; Jones & Comfort, 2019 ; Prayag et al, 2019 ; Ritchie & Jiang, 2019 ; Tibay et al, 2018 ). In this regard, the tourism industry fits into the socio-ecological systems, considered as a reference for resilience studies.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The vulnerability of the tourism sector justifies the growing interest in the literature on the topic of resilience (e.g., Chowdhury, Prayag, Orchiston, & Spector, 2019 ; Jones & Comfort, 2019 ; Prayag et al, 2019 ; Ritchie & Jiang, 2019 ; Tibay et al, 2018 ). In this regard, the tourism industry fits into the socio-ecological systems, considered as a reference for resilience studies.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Regarding the former, it is worth mentioning the works of Calgaro et al (2014) , Espiner and Becken (2014) and Filimonau and De Coteau (2019) . Micro-level studies include Biggs, Hall, and Stoeckl (2012) , which analyses the resilience of formal and informal tourism enterprises to disasters; Chowdhury et al (2019) , which explore the links between social capital, adaptive resilience and business performance of tourism organisations (e.g., accommodation, transport); and Kutzner (2019) , which examines the socio-ecological resilience of tour operators, among others. In terms of the study issue, topics such as resilience to disasters (e.g., Ivkov et al, 2019 ), climate change (e.g., Dogru, Marchio, Bulut, & Suess, 2019 ) or economic crisis (e.g., Cellini & Cuccia, 2015 ) have been analysed.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…For example, human capital (employees' adaptive capacity and individual resilience) and lifestyle identify (owners and mangers' lifestyle choice and satisfaction) are seen as important in achieving resilience in tourism organizations (Biggs, ; Prayag et al, ). The strength of business ties in relation to other stakeholders (e.g., trust, commitment, and friendship) has a strong influence on adaptive resilience (Chowdhury, Prayag, Orchiston, & Spector, ). Orchiston () further adds to this discussion by highlighting continuity insurance and staff induction as the most commonly used tools to achieve tourism resilience in the context of the Southern Alps of New Zealand.…”
Section: Environmental Uncertainty Tourism Organizational Resiliencementioning
confidence: 99%
“…The accommodation and F&B sector are able to service the needs of community needs after disasters (Hystad & Keller, ), such as using Airbnb accommodation to provide homes for tourists and aid workers (Hajibaba, Karlsson, & Dolnicar, ). Furthermore, informal (or small) tourism organizations (e.g., in family ownership) usually have lower capital investment than formal (or large) tourism organizations but have higher levels of social capital from the community (Biggs et al, ), which is found to be positively related with organizational resilience (Brown et al, ; Calgaro & Lloyd, ; Chowdhury et al, ).…”
Section: Dynamic Capabilities Approach To Achieve Resilience In Crisementioning
confidence: 99%
“…These external factors, besides the serious reliance on inbound visitors and destination marketing organizations, leads to increased sudden shocks to the tourism industry (Orchiston and Higham 2016). However, organizational resilience should not be explained partly from business performance since there are external factors that tourism organizations have little control over (Chowdhury et al,2018). XIAO and CAO (2017) defined organizational resilience as the organization"s talent to reinstate to a stable situation and even creates a new ability in disrupting conditions.…”
Section: Orgnizational Resiliencementioning
confidence: 99%